Halophilic Bacteria as a Source of Novel Hydrolytic Enzymes - Encarnación Mellado; María Teresa García; Dolores Pérez; María de Lourdes Moreno (Life, 2013)
Hydrolases constitute a class of enzymes widely distributed in nature from bacteria to higher eukaryotes. The halotolerance of many enzymes derived from halophilic bacteria can be exploited wherever enzymatic transformations are required to function under physical and chemical conditions, such as in the presence of organic solvents and extremes in temperature and salt content. In recent years, different screening programs have been performed in saline habitats in order to isolate and characterize novel enzymatic activities with different properties to those of conventional enzymes. Several halophilic hydrolases have been described, including amylases, lipases and proteases, and then used for biotechnological applications. Moreover, the discovery of biopolymer-degrading enzymes offers a new solution for the treatment of oilfield waste, where high temperature and salinity are typically found, while providing valuable information about heterotrophic processes in saline environments. In this work, we describe the results obtained in different screening programs specially focused on the diversity of halophiles showing hydrolytic activities in saline and hypersaline habitats, including the description of enzymes with special biochemical properties. The intracellular lipolytic enzyme LipBL, produced by the moderately halophilic bacterium Marinobacter lipolyticus, showed advantages over other lipases, being an enzyme active over a wide range of pH values and temperatures. The immobilized LipBL derivatives obtained and tested in regio- and enantioselective reactions, showed an excellent behavior in the production of free polyunsaturated fatty acids (PUFAs). On the other hand, the extremely halophilic bacterium, Salicola marasensis sp. IC10 showing lipase and protease activities, was studied for its ability to produce promising enzymes in terms of its resistance to temperature and salinity.